The Effect of a Standing Intervention on Falls in Long Term Care: a Secondary Analysis of a Randomized Controlled Trial. - Gallibois, Molly; Handrigan, Grant; Caissie, Linda; Cooling, Kendra; Hébert, Jeffrey; Jarrett, Pamala; McGibbon, Chris; Read, Emily; Sénéchal, Martin; Bouchard, Danielle R. (Canadian Geriatrics Journal, 2023)
Background Older adults in long term care (LTC) spend over 90% of their day engaging in sedentary behaviour. Sedentary behaviour may exacerbate functional decline and frailty, increasing the risk for falls. The purpose of this study is to explore the impact of a 22-week standing intervention on falls among LTC residents at 12-month follow-up. Methods This was a planned secondary analysis of the Stand if You Can randomized controlled trial. The original trial randomized 95 participants (n = 47 control; n = 48 intervention) to either a sitting control or a supervised standing intervention group (100 minutes/week) for 22 weeks. Falls data were available to be collected over 12 months post-intervention for 89 participants. The primary outcome was a hazard of fall (Yes/No) during the 12-month follow-up period. Results A total of 89 participants (average age 86 years ± 8.05; 71.9% female) were followed for 12-months post-intervention. Participants in the intervention group (n=44) had a significantly greater hazard ratio of falls (2.01; 95% CI = 1.11 to 3.63) than the control group (n=45) when accounting for the history of falls, frailty status, cognition level, and sex. Conclusion Participants who received a standing intervention over 22 weeks were twice as likely to fall 12 months after the intervention compared with the control group. However, the prevalence of falls did not surpass what would be typically observed in LTC facilities. It is imperative that future studies describe in detail the context in which falls happen and collect more characteristics of participants in the follow-up period to truly understand the association between standing more and the risk of falls.